The phytochemistry of several South African aloe species - McCarthy, Terence John (Rhodes University, Faculty of Pharmacy, Pharmacy, 1967)
Introduction: Despite the tremendous advances made with regard to synthetic organic medicinals within the last two decades, heavy reliance is still placed on plant products. This is especially true of the anthracene derivatives used medicinally as purgatives, and which are derived principally from senna, cascara, rhubarb, frangula and aloes. While particular attention has been paid to the chemistry of the former group in recent years, aloes has been largely neglected, possibly due to the fact that the Aloe species are confined largely to areas where extensive research facilities are lacking, such as Africa , India and the West Indies. Thus research in Europe has been confined largely to the lump aloes of commerce, derived from relatively few species. In 1953 a comprehensive report by Hodge (103) appeared on "The Drug Aloes of Commerce, with Special Reference to the Cape Species". Hodge observed that South Africa abounds in species just as abundant as A.ferox, (which is the prime source of Cape aloes), and advised that a systematic chemical survey might show certain of these to be not only higher yielders of bitter aloetic juice but also sources of a superior drug product. Consequently an investigation along these lines is presented here, and it is observed that several species apart from A.ferox not only contain aloin, but also yield a large volume of aloetic juice. Only pharmacologic studies can reveal if the juice of these species is as safe as that of A.ferox, but without doubt they could be used for the extraction of crystalline aloin. Concurrently, the distribution of the Aloe resins, said by some to be purgative themselves, has been studied. The investigation has revealed that the structurally similar compound homonataloin enjoys an equally wide distribution as aloin. However, almost invariably it is confined to small species yielding little aloetic juice, apart from which nothing is known regarding its pharmacologic properties. It is interesting to note that the resin distribution in the homonataloin-containing species is very similar to that of the aloin-containing species, but differs widely from. that of the species containing neither of these principles. Apart from aloin and homonataloin, aloinoside and chrysophanol also occur in Aloe species, and together with the resins, these indicate that when all the South African Aloe species have been investigated, they may well be of chemotaxonomic value. Within the comparatively short space of the last decade some work has been performed on aspects of the metabolism of such anthracene-containing species as Rheum, Rhamnus and Rumex. These investigations have shown that the anthracene derivatives are not merely waste products, but perform definite metabolic functions. The latter portion of this work has been devoted to this relatively neglected aspect of the Aloe species.
Keywords: Botanical chemistry; Aloe -- Research -- South Africa; Aloe -- Analysis; Medicinal plants -- Research -- South Africa; Drugs -- Research; Chromatographic analysis